Investigating Equivoque in Marzbannameh as a Stylistic Feature - Zeinab Rezapour (نثرپژوهی ادب فارسی, 2022)
Marzbannameh is one of the brilliant examples of technical prose in the seventh century AH, which, despite its high status, some of the aesthetic aspects and artistic accuracy of this great literary work have remained unknown. This research uses a descriptive-analytical method to explain and analyze the “Equivoque” in Marzbannameh as one of the hidden stylistic features. This innovative figure of speech has provided a good context for creating forms of imagination, metonymy, textual coherence, and development of intensions and meanings in texts. A review on the definitions of this type of ambiguity and also the study of the types and functions of this figure of speech in Marzbannameh are the topics investigated in this research. The results of the research indicate that Equivoque in Marzbannameh does not fall within the definitions of this figure only, and it has effects in different levels of word, composition, sentence and beyond with usages such as creating various literary techniques such as implicit similes, allusions, irony, and expanding and reinforcing meaning, developing and completing meaning in the formation of various contextual layers and multidimensionality. Many of the ambiguities of Marzbannameh are created vertically in connection with the preceding and subsequent clauses and are not limited to one or two sentences.